Silicon Transporters and Effects of Silicon Amendments in Strawberry under High Tunnel and Field Conditions - Ouellette, Samuel; Goyette, Marie-Hélène; Labbé, Caroline; Laur, Joan; Gaudreau, Linda; Gosselin, André; Dorais, Martine; Deshmukh, Rupesh K.; Bélanger, Richard R. (Frontiers in Plant Science, 2017)
Together with longer production periods, the commercial transition to day-neutral strawberry (Fragaria X ananassa) varieties has favored the development of diseases such as powdery mildew (Podosphaera aphanis) that thrives in late summer-early fall. In an attempt to find alternative solutions to fungicides currently employed to curb the disease, we wanted to investigate the potential of silicon (Si) amendments that have been associated with prophylactic properties against powdery mildews. To this end, our first objective was to determine if strawberry was a Si-competent species following the recent characterization of the properties of Si transporters that plants must carry to uptake silicic acid. Based on genomic data, we were able to conclude that strawberry contained both functional influx (Lsi1) and efflux (Lsi2) transporters for Si uptake. Subsequently commercial experiments under high tunnel and field conditions were conducted with different Si fertilization regimes: constant soluble Si feeding in high tunnel, and bi-weekly soluble Si feeding or three concentrations of calcium silicate fertilization in the field. Results from high tunnel experiments showed that strawberry could accumulate as much as 3% Si on a dry-weight basis, the highest concentration ever reported for this species. All six tested cultivars contained roughly the same concentration, thereby confirming the limited genetic variability, also observed in other species, associated with the trait. Silicon fertilization under high tunnel led to a significant reduction of powdery mildew severity in both years and on all cultivars, and a significant increase in yield of marketable fruits reaching as much as 300% with cv. Monterey. By contrast, Si fertilization under field conditions in soils deficient in plant available Si, either in soluble or solid form, did not result in significant accumulation of Si in plants, regardless of the cultivars, year or concentrations. Our results have thus provided both genotypic and phenotypic proof that strawberry can greatly benefit from Si fertilization, but have also highlighted the importance of validating the fertilization regime to ensure that Si is properly absorbed and/or available to the plant.